2020
DOI: 10.3390/microorganisms8091270
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Bacterial Community in Producing a Peculiar Smell in Chinese Fermented Sour Soup

Abstract: In this paper, the volatile flavour constituents and the bacterial diversity in characteristic Chinese fermented sour soup were analysed, and the dynamics of bacteria associated with the odour were characterized. The bacterial diversity of sour soup was studied by high-throughput sequencing. A total of 10 phyla and 89 genera were detected. Firmicutes was the dominant phylum of sour soup, accounting for 87.14–98.57%. The genus structure of normal sour soup was relatively simple, and Lactobacillus (78.05–90.26%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…These bacteriocins serve as natural antimicrobial agents and increase the safety of food products. Apart from bacteriocins, LAB also produces metabolites that contribute to the flavor, taste, and odor of sour soup [8]. A recent study reported the presence of aldehydes and butyric acid as the causative agents of foul odor in sour soup [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These bacteriocins serve as natural antimicrobial agents and increase the safety of food products. Apart from bacteriocins, LAB also produces metabolites that contribute to the flavor, taste, and odor of sour soup [8]. A recent study reported the presence of aldehydes and butyric acid as the causative agents of foul odor in sour soup [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported the presence of aldehydes and butyric acid as the causative agents of foul odor in sour soup [9]. Metagenomic (Illumina MiSeq) sequencing and metabolomic investigation of fermented Chinese sour soup detected 89 bacterial genera and 51 aromatic compounds (including 25 esters, eight alcohols, eight terpenes, three sulfur compounds, two acids, two ketones, one aldehyde, one pyrazine, and one monoterpene) in sour soup [8]. Metagenomic sequencing can be used to analyze millions of DNA sequences at the same time for the dissection of the genetic makeup of the microbial community to predict their functions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, selecting suitable microbial strains to standardize the fermentation process, shorten the fermentation cycle, and stabilize the flavor quality of the product is necessary. Although there have been studies on the flavor and microbial communities of sour soup, and the microbial flora [ 12 , 13 , 14 , 15 , 16 ], there are few studies on the VFCs of tomato sour soup that use the inoculation of dominant bacteria, or on the relationship between the change in microbial communities and VFC generation in the CTN fermentation process used to enhance fermentation. Therefore, improving the quality of CTN is necessary to study the succession of microbial communities, the change in VFCs, their relationship during CTN fermentation, and the influence of enhanced fermentation by dominant bacteria on the quality of tomato sour soup.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HTS was used to analyze bacteria in tomato sour soup, in which Lacticaseibacillus spp. was found to be the dominant bacteria [ 16 ]. The microbial structure of fermented foods often has an effect on flavor substances; however, the relationship between these microbiota and flavor is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%